Cell-Penetrating Peptide and siRNA-Mediated Therapeutic Effects on Endometriosis and Cancer In Vitro Models - Kristina Kiisholts; Kaido Kurrikoff; Piret Arukuusk; Ly Porosk; Maire Peters; Andres Salumets; Ülo Langel (Pharmaceutics, 2021)
Gene therapy is a powerful tool for the development of new treatment strategies for various conditions, by aiming to transport biologically active nucleic acids into diseased cells. To achieve that goal, we used highly potential delivery vectors, cell-penetrating peptides (CPPs), as oligonucleotide carriers for the development of a therapeutic approach for endometriosis and cancer. Despite marked differences, both of these conditions still exhibit similarities, like excessive, uncoordinated, and autonomous cellular proliferation and invasion, accompanied by overlapping gene expression patterns. Thus, in the current study, we investigated the therapeutic effects of CPP and siRNA nanoparticles using in vitro models of benign endometriosis and malignant glioblastoma. We demonstrated that CPPs PepFect6 and NickFect70 are highly effective in transfecting cell lines, primary cell cultures, and three-dimensional spheroids. CPP nanoparticles are capable of inducing siRNA-specific knockdown of therapeutic genes, ribonucleotide reductase subunit M2 (RRM2), and vascular endothelial growth factor (VEGF), which results in the reduction of in vitro cellular proliferation, invasion, and migration. In addition, we proved that it is possible to achieve synergistic suppression of endometriosis cellular proliferation and invasion by combining gene therapy and hormonal treatment approaches by co-administering CPP/siRNA nanoparticles together with the endometriosis-drug danazol. We suggest a novel target, RRM2, for endometriosis therapy and as a proof-of-concept, we propose a CPP-mediated gene therapy approach for endometriosis and cancer.